COVID-19 vaccine hesitancy: A narrative review of four South Asian countries - Farah Ennab; Rakhtan K. Qasba; Utkarsha Uday; Priya Priya; Khulud Qamar; Faisal A. Nawaz; Zarmina Islam; Nabil Zary (Frontiers Media S.A., 2022)
ObjectivesVaccine hesitancy remains a global issue, especially within poverty-stricken countries where there's an interplay of financial and non-financial barriers. This narrative review aims to understand attitudes and behaviors toward COVID-19 vaccination in four South Asian countries and make context-specific recommendations to vaccine program drivers and decision-makers.MethodsA search was conducted using PubMed and Science Direct, and CINHAL from January 2020 up to May 2022 restricted to the English language for terms: "Afghanistan" OR "Pakistan" OR "India" OR "Bangladesh" in combination with "COVID-19 vaccine" and other related terms. All articles were initially included, and those with relevance were included in the synthesis of this paper.ResultsA narrative review was performed for this study. Our narrative review included a total of eighteen studies with a sample size (n = 223-5,237) averaging about 1,325 participants per study conducted. The studies included revealed public hesitancy to receive the COVID-19 vaccine ranging from 6.3 to 56.2% with an average of 31.63% across all eighteen studies. Several reasons were linked to this observation in these four South Asian countries, and the predominant ones included: Insufficient information provided to the general public about the side effects of the vaccines, concerns regarding vaccine safety, and skepticism of vaccine efficacy.ConclusionVaccine hesitancy is a global problem within the context of COVID-19, and issues regarding equity, misinformation, and poverty in South Asian countries makes it difficult to meet goals for herd immunity. Policymakers and governments should aim toward financial and non-financial incentives to drive the public toward vaccination.